Faktor-Faktor yang Mempengaruhi Sikap ketika Menyaksikan Iklan di Televisi - Abdul Holik; Rini Handayani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research attempts to find several factors influencing students’ attitudes when watching commercial advertisements on television. The data used here is taken from surveying over 148 respondents who are university students. The method used is multivariate regression trying to find the impact of independent variables on the dependent variable. From the estimation result, we find that only economic conditions and forms of advertisement can be able to affect the attitude of respondents. All other independent variables, namely intellectuality, family background, and social circumstances, cannot alter anything of the dependent variable. This finding informs us that various forms of advertisement are not so important to involve the intellectuality of the audiences, family background, and social condition. This research can enrich discourses regarding efficient ways for many firms to attract audiences’ attention positively.